2012
DOI: 10.4172/2155-9880.s11-001
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Cardiac Stem Cell Therapy

Abstract: Cardiac Progenitor Cells (CPCs) are multipotent cells of the myocardium. They are located inside niches of the heart muscle, can be isolated, characterized and used for cardiac regeneration in stem cell therapy. Actually, CPCs may be isolated by tissue digestion with or without cell sorting, but it is difficult to achieve the maximum level of differentiation when these cells are implanted into a damaged myocardium.The knowledge recently acquired on small molecules of non-coding RNAs, microRNA (miRNA), may impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In our previous review, mentioned few cases as biomarker for cardiologists, hereby, this study summarizes the cuttingedge applications of miRNA. In a recent study by Serradifalco et al proved that nanoparticle bearing miRNAs reprogrammed CPCs in a biodegradable 3D scaffold [40,41]. Now, these molecules have great potential to understanding the pathophysciology and offer a novel class of biomarkers for acute myocardial infarction diagnosis.…”
Section: Clinical Significance Of Mirnasmentioning
confidence: 99%
“…In our previous review, mentioned few cases as biomarker for cardiologists, hereby, this study summarizes the cuttingedge applications of miRNA. In a recent study by Serradifalco et al proved that nanoparticle bearing miRNAs reprogrammed CPCs in a biodegradable 3D scaffold [40,41]. Now, these molecules have great potential to understanding the pathophysciology and offer a novel class of biomarkers for acute myocardial infarction diagnosis.…”
Section: Clinical Significance Of Mirnasmentioning
confidence: 99%
“…Regarding heart regeneration and the role of miRNAs, studies have reported that the molecules are capable to reprogramme the CSCs to attain three dimensional structure of cardiac muscle in its correct orientation. To put forth the applications of miRNAs in cardiac regeneration, recent studies have proved that nanoparticle bearing miRNAs are able to reprogramme isolated CPCs in a biodegradable tolerated 3D scaffold [19].…”
Section: Microrna As Cardiac Biomarkermentioning
confidence: 99%
“…[5][6][7] MiRs target most human protein coding genes; especially miR-499 encoded by myosin gene family shows a high expression in circulation in patients with AMI. 8 It is involved in the structural and functional differentiation of cardiac stem cell into cardiomyocytes 9 and also plays a pivotal role in the recovery of cardiac cell, following injury. 10,11 Few studies in the recent past have shown that miR in body fl uids are highly stable and become specifi c molecular signatures for diseases thus enabling them as markers of diagnosis as well as prognosis.…”
Section: Introductionmentioning
confidence: 99%